I am avoiding it! a seniors' perspectives about advertising - Loureiro, S. (2015)
The aims are to analyze (i) the relationship between drivers to ad avoidance among senior viewers and (ii) compare the perceptions about those drivers between TV advertising and YouTube advertising. Findings reveal that irritation seems to be the crucial factor that lead consumers to avoid whacking advertisings. A negative attitude toward advertising and skepticism do not mediate the effect between advertising irritation and avoidance.